Alkenones in oceanic odontocetes as a potential proxy of environmental water temperature - Diego Rita (Elsevier, 2021)
The alkenones C37:2 and C37:3 are produced exclusively by some haptophyte species. Their relative proportion (Uk’37 index) may be used to infer the water temperature where the synthesising haptophyte lived. Alkenones have been analysed in sediments, planktonic communities and in the low trophic level, filter-feeding fin whales. However, it is unclear whether they can be detected in animals exploiting high trophic levels and used to infer the water temperature in which they live. Alkenones were analysed in blubber samples from three Mediterranean predatory species: the striped dolphin, an epipelagic species; the Risso’s dolphin, a deep diver; and the bottlenose dolphin, a coastal species. Alkenones were detected in all striped dolphin samples and in most of the Risso’s dolphin samples, but they were below detection limits in the bottlenose dolphin samples. The inferred temperature for the striped dolphins (16.4 ± 3.3 °C) was similar to the average water temperature of the region (16.9 ± 3.9 °C), but that for the Risso’s dolphins was lower than expected (12.7 ± 4.4 °C). The small sample sizes and the large variance in the Uk’37 index make it difficult to ascertain if the dissimilarity between the two oceanic species is real. Although further research is needed to calibrate this bio-indicator, we can conclude that alkenones are transferred through the trophic web and are found in oceanic cetaceans situated at a high trophic level.